2017
DOI: 10.1080/21645515.2017.1342020
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, open-label clinical trial to evaluate immunogenicity and safety of an indigenously developed DTwP-Hib tetravalent combination vaccine (Easyfour®-TT) with Quadrovax® in Indian infants

Abstract: CTRI/2014/12/005326 (registered with the Clinical Trial Registry of India (CTRI)).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…The use of the ECL assay for the evaluation of the pertussis response in our study provides data that are precise, accurate, and reproducible [8] . Commercially available assays developed for routine pertussis diagnostic purposes that have been used in the evaluation of pertussis immunogenicity in many other clinical studies of wP-containing vaccines [28] , [29] , [30] , [31] , [32] , [41] , [42] , [43] have unknown specificity and are less well-suited to the robust evaluation that is required in clinical trials. Additionally, the pertussis component of the DTwP-IPV-HB-PRP∼T vaccine is similar to that contained in an established range of vaccines (DTCoq, Tetracoq, Pentacoq) that have been used extensively and have shown efficacy and field effectiveness against pertussis [44] , [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of the ECL assay for the evaluation of the pertussis response in our study provides data that are precise, accurate, and reproducible [8] . Commercially available assays developed for routine pertussis diagnostic purposes that have been used in the evaluation of pertussis immunogenicity in many other clinical studies of wP-containing vaccines [28] , [29] , [30] , [31] , [32] , [41] , [42] , [43] have unknown specificity and are less well-suited to the robust evaluation that is required in clinical trials. Additionally, the pertussis component of the DTwP-IPV-HB-PRP∼T vaccine is similar to that contained in an established range of vaccines (DTCoq, Tetracoq, Pentacoq) that have been used extensively and have shown efficacy and field effectiveness against pertussis [44] , [45] , [46] .…”
Section: Discussionmentioning
confidence: 99%
“…11 World Health Organization (WHO) has promoted the use of combination vaccines for immunization programs in 2017. 12 Countries, notably the US, Canada, and India, have introduced the DTaP-IPV-Hib combination vaccine into the routine childhood immunization program, replacing the separated DTaP, IPV, and Hib vaccines. In China, the DTaP-IPV-Hib combination vaccine has been approved; however, it is not integrated into NIP.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic evaluation and meta‐analysis also suggested that the DTaP‐IPV‐Hib combination vaccine and separate vaccines did not differ concerning immunogenicity parameters 11 . World Health Organization (WHO) has promoted the use of combination vaccines for immunization programs in 2017 12 . Countries, notably the US, Canada, and India, have introduced the DTaP‐IPV‐Hib combination vaccine into the routine childhood immunization program, replacing the separated DTaP, IPV, and Hib vaccines.…”
Section: Introductionmentioning
confidence: 99%